Monetary Policy and Foreign Exchange Management: Reforming Central Bank Functions in Myanmar - Bandid Nijathaworn; Suwatchai Chaikhor; Suppakorn Chotika-arpa; Suchart Sakkankosone (Asian Development Bank (ADB), 2015)
Myanmar's macroeconomic policy framework does not adequately support the new functions of the Central Bank of Myanmar. The monetary policy regime is deficient and institutions that complement the working of a market-based economy lacking. This paper identifies 10 priority areas for reform to allow the central bank to effectively perform its emerging new functions in support of economic growth and stability. This is a three-front effort: dismantle nonmarket arrangements, especially in the finance sector; implement a monetary policy framework and operational procedures, including financial markets development; and enhance central bank policy capacity. The latter includes elevating the policy process, central banking functions, and institutional roles to match the tasks of a modern monetary authority in a market-based economy.
hdl:11540/4345
Keywords: E51; E52; E58; 330; central bank; financial markets; monetary policy; Myanmar